The death throes of the old spanish system of liability for environmental damage - Valencia Martín, Germán (2013)
This paper analyzes the last judgments in the case of the Aznalcóllar mines (or Boliden case). A well-known event in Spain that produced significant environmental damage, and that, having occurred before the new Law on Environmental Liability and to be resolved under the previous legislation, is causing countless problems for reimbursement of the substantial expenditures invested by the Spanish Public Administration inrepairing the damage. Posed a negative conflict of jurisdiction between civil and administrative courts, the Special Chamber of Conflicts of Jurisdiction of the Supreme Court has just returned the matter back to the former. To the author, it is, however, a false or apparent conflict, because of loopholes in that previous law, fortunately overcome for the future.